2009
DOI: 10.1111/j.1479-828x.2008.00943.x
|View full text |Cite
|
Sign up to set email alerts
|

Labial fusion causing acute urinary retention in a young adult: A case report

Abstract: Figure 1 Labial fusion with a small opening. Clinical-Scientific Notes 116

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…There are few reports of labial adhesion occurring at a reproductive age. A PubMed search using the index words ‘labial adhesion’ or ‘labial fusion’ yielded 26 such cases, with reproductive age tentatively defined as 15–50 years of age 3–26 . In 22 of these 26 cases, the etiological factors were confirmed or speculated as perineal injuries after vaginal delivery (11 cases), 7–16 genital herpes infection (eight cases), 17–23 female circumcision (two cases), 24,25 and genital graft‐versus‐host disease after hemopoietic stem cell transplantation (one case) 26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are few reports of labial adhesion occurring at a reproductive age. A PubMed search using the index words ‘labial adhesion’ or ‘labial fusion’ yielded 26 such cases, with reproductive age tentatively defined as 15–50 years of age 3–26 . In 22 of these 26 cases, the etiological factors were confirmed or speculated as perineal injuries after vaginal delivery (11 cases), 7–16 genital herpes infection (eight cases), 17–23 female circumcision (two cases), 24,25 and genital graft‐versus‐host disease after hemopoietic stem cell transplantation (one case) 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In 22 of these 26 cases, the etiological factors were confirmed or speculated as perineal injuries after vaginal delivery (11 cases), 7–16 genital herpes infection (eight cases), 17–23 female circumcision (two cases), 24,25 and genital graft‐versus‐host disease after hemopoietic stem cell transplantation (one case) 26 . In the remaining four cases, 3–6 the causes were unclear (Table 1). In the four cases hitherto reported, the diagnosis was made at age 18, 20, 22, and 30 years of age and complaints were coital difficulty or urinary retention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the acute onset of voiding symptoms and urinary retention in our case does not support this theory. Topcuoglu et al [8] reported an 18-year-old girl who presented with acute urinary retention. Labial fusion was diagnosed without any detectable etiological factors.…”
Section: Discussionmentioning
confidence: 99%
“…Kuo et al [6] 30 Difficult coitus Surgical adhesiolysis No recurrence at 6 months Topcuoglu et al [8] 18 Urinary retention Surgical adhesiolysis+ topical estrogen No recurrence at 5 months Kutlu et al [7] 22 Urinary retention Surgical adhesiolysis Not described…”
Section: Discussionmentioning
confidence: 99%